Double-hole transmission structure, inorganic light-transmitting solar cell based on double-hole transmission structure and preparation method of inorganic light-transmitting solar cell
By adopting a double hole transport structure in translucent perovskite solar cells and using efficient organic materials and stable inorganic materials, the problems of poor stability and low efficiency of solar cells in the prior art are solved, and efficient and stable inorganic translucent perovskite solar cells are realized, which is suitable for large-scale applications in the field of building photovoltaics.
Patent Information
- Application Number
- CN202411682528.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-11
AI Technical Summary
Existing light-transmitting perovskite solar cells have poor stability in the natural environment, and commonly used organic hole transport materials are inefficient and susceptible to damage.
A double hole transport structure is adopted, wherein the first hole transport layer is prepared from an efficient organic material such as Spiro-OMeTAD, PTAA or P3HT, and the second hole transport layer is prepared from a stable inorganic material such as nickel oxide, cuprous iodide, copper oxide or vanadium pentoxide, and the stability and efficiency of the layer are ensured through technologies such as slit coating and electron beam deposition.
It realizes efficient and stable inorganic light-transmitting perovskite solar cells, has high light transmittance and photoelectric conversion efficiency, and maintains stability in the natural environment, and is suitable for large-scale applications in the field of building photovoltaics.
Smart Images

Figure CN119604115A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy and solar cell, and in particular to a double hole transport structure and an inorganic light-transmitting solar cell based on the structure and a preparation method thereof. Background Art
[0002] Light-transmitting perovskite solar cells (ST-PSCs) are combined with building exterior walls and car windows to balance the photoelectric conversion efficiency and visible light transmittance, and are expected to achieve functions such as building production capacity and carbon reduction. The structure of a common light-transmitting solar cell includes a transparent conductive substrate, an electron transport layer, a perovskite light-absorbing layer, a hole transport layer, and a transparent conductive electrode. Among them, there are many choices for the material of the perovskite light-absorbing layer. Organic-inorganic hybrid perovskites have strong light absorption properties in the visible light range due to their narrow band gap, which seriously affects the transmittance of the battery. Metal halide perovskites have many advantages such as adjustable band gap, high absorption coefficient, and long carrier diffusion length. They are ideal light-absorbing materials for light-transmitting solar cells. In addition, by adjusting the film thickness and band gap of the metal halide perovskite light-absorbing layer, solar cells with different transmittances can be obtained in the visible light region.
[0003] The material and structure of the hole transport layer are also very important for the performance of light-transmitting solar cells. Currently, common organic hole transport materials are easily affected by factors such as high temperature, high humidity, and oxygen, resulting in poor stability and short life of solar cells in the natural environment. Inorganic hole transport materials with better stability are prone to damage to perovskite crystals due to their inefficient carrier mobility and poor deposition process.
[0004] In summary, the development of an inorganic light-transmitting solar cell based on an efficient and stable hole transport layer is of vital importance to achieving carbon reduction in buildings. Summary of the invention
[0005] One of the purposes of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a multi-hole transport structure, which at least includes a first hole transport layer and a second hole transport layer, wherein the second hole transport layer is closely attached to the first hole transport layer.
[0006] Furthermore, the material of the first hole transport layer is selected from any one of Spiro-OMeTAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene), PTAA (Poly[bis(4-phenyl)(2,4,6-triMethylphenyl)aMine]), and P3HT (poly(3-hexylthiophene)).
[0007] Furthermore, the thickness of the first hole transport layer is 2nm-50nm.
[0008] Furthermore, the material of the second hole transport layer is selected from nickel oxide (NiO X ), cuprous iodide (CuI), copper oxide (CuO X ), any one of vanadium pentoxide (V2O5).
[0009] Furthermore, the thickness of the second hole transport layer is 10nm-40nm.
[0010] The second object of the present invention is to provide a method for preparing the above-mentioned multi-hole transport structure, including: preparing a first hole transport layer on a substrate by slit coating, and preparing a second hole transport layer on the surface of the first hole transport layer by electron beam deposition or radio frequency power magnetron sputtering.
[0011] Furthermore, the preparation process of the first hole transport layer is as follows: Spiro-OMeTA D, PTAA or P3HT is evenly mixed with an organic solvent (such as chlorobenzene or toluene solvent) to prepare a solution with a concentration of 1-5 g / L, and then the solution is coated on the substrate at a rate of 5-10 mm / s using a slit coating technique, and the first hole transport layer is obtained after sufficient drying.
[0012] Furthermore, the preparation process of the second hole transport layer is as follows: using electron beam deposition or magnetron sputtering technology, respectively The speed of NiO X 、CuI、CuO X Or V2O5 is deposited on the surface of the first hole transport layer multiple times to obtain the second hole transport layer. The main purpose of multiple depositions is to prevent high-speed and high-energy particles from penetrating the first hole transport layer during electron beam deposition or magnetron sputtering and destroying the perovskite light absorption layer.
[0013] The third object of the present invention is to provide an inorganic light-transmitting solar cell based on the above-mentioned multi-hole transport structure, which has a multi-layer structure, and includes, from bottom to top or from top to bottom, a transparent conductive substrate, an electron transport layer, a perovskite light absorption layer, a first hole transport layer, a second hole transport layer, and a transparent conductive electrode.
[0014] Furthermore, the transparent conductive substrate is specifically tin dioxide (FTO) or indium tin oxide (ITO) glass.
[0015] Furthermore, the electron transport layer is specifically SnO2, and has a thickness of 10nm-20nm.
[0016] Furthermore, the perovskite light-absorbing layer is specifically CsPbBr3, and has a thickness of 500nm-600nm.
[0017] Furthermore, the transparent conductive electrode is specifically indium tin oxide (ITO), indium zinc oxide (IZO) or indium tungsten oxide (IWO).
[0018] The fourth object of the present invention is to provide a method for preparing the above-mentioned inorganic light-transmitting solar cell, comprising: washing and drying the transparent conductive substrate, preparing an electron transport layer on its surface by chemical bath deposition, spraying, atomic layer deposition or magnetron sputtering, and then preparing a perovskite light-absorbing layer on the surface of the electron transport layer by thermal evaporation, and then preparing a first hole transport layer and a second hole transport layer on the surface of the perovskite light-absorbing layer in sequence according to the aforementioned method, and finally preparing a transparent conductive electrode on the second hole transport layer by magnetron sputtering or atomic layer deposition.
[0019] Compared with existing similar products or technologies, the advancement or beneficial effects of the present invention are mainly reflected in the following aspects:
[0020] (1) Existing light-transmitting perovskite solar cells are mainly based on unstable organic functional layer materials, which not only show low transmittance in the visible light region, but also have obvious stability problems in the natural environment. For this reason, the present invention selects efficient organic materials and stable inorganic materials to prepare a new double hole transport layer that has both advantages, and selects stable, wide-bandgap inorganic materials to prepare the perovskite light absorption layer, and finally obtains a stable and efficient inorganic light-transmitting perovskite solar cell.
[0021] (2) All functional layers in the light-transmitting perovskite solar cell prepared by the present invention are highly transparent films, which not only have high light transmittance and photoelectric conversion efficiency, but also can be stably stored in the natural environment. It also overcomes the problem that ordinary solution technology is difficult to scale up, and realizes large-scale production. It can be widely used in architectural glass and automotive glass, and ultimately promote the large-scale application of photovoltaic films in the fields of construction and so on.
[0022] (3) The first hole transport layer of the present invention is prepared from an efficient organic hole transport material and is prepared by a non-destructive scraping technique; the second hole transport layer is prepared from a stable inorganic hole transport material and requires high-energy electron beam deposition or magnetron sputtering technology for preparation. The first hole transport layer can slow down or reduce the damage to the perovskite caused by high-energy particles generated by the second hole transport layer during electron beam deposition or magnetron sputtering, thereby protecting the perovskite and improving the charge transfer inside the battery, and finally obtaining a stable and efficient inorganic light-transmitting perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1The morphology of the perovskite films prepared in Example 1 and Comparative Examples 1 and 2;
[0024] Figure 2 JV curves of ST-PSCs prepared in Example 1 and Comparative Examples 1 and 2;
[0025] Figure 3 The transmittance curves of ST-PSCs prepared in Example 1 and Comparative Examples 1 and 2;
[0026] Figure 4 The environmental stability test diagram of ST-PSCs prepared in Example 1 and Comparative Examples 1 and 2;
[0027] Figure 5 This is a JV curve diagram of the semi-transparent perovskite photovoltaic module prepared in Example 2;
[0028] Figure 6 Dimensional diagram of ST-PSCs prepared in Example 1;
[0029] Figure 7 This is a dimensional diagram of the semi-transparent perovskite photovoltaic module prepared in Example 2;
[0030] Figure 8 This is a dimensional diagram of the semi-transparent perovskite photovoltaic module prepared in Example 3;
[0031] Fig. 9 This is a dimensional diagram of the semi-transparent perovskite photovoltaic module prepared in Example 4;
[0032] Fig.10 This is a physical picture of the semi-transparent perovskite photovoltaic module prepared in Example 4. DETAILED DESCRIPTION
[0033] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, further description is given below in conjunction with specific embodiments and drawings.
[0034] The preparation process of the inorganic ST-PSC based on the double hole transport structure provided by the present invention comprises the following steps:
[0035] S1. Fully clean the transparent conductive substrate using non-woven fabric, detergent, deionized water, anhydrous ethanol, etc. The substrate is specifically any one of commercial fluorine-doped tin dioxide (FTO) or indium tin oxide (ITO) glass.
[0036] S2. Prepare SnO2 electron transport layer on transparent conductive substrate by any one of chemical bath deposition, spraying, atomic layer deposition or magnetron sputtering. For chemical bath deposition, the transparent conductive substrate is immersed in SnO2 solution with a concentration of 1.5-2mmol / L and a temperature of 80-90℃ to deposit SnO2 with a thickness of 20-40nm; for spraying, a SnO2 solution with a concentration of 0.5-0.6mol / L is sprayed onto the transparent conductive substrate, during which nano SnO2 particles are deposited on the transparent conductive substrate with a thickness of 20-40nm; for atomic layer deposition, the growth rate of SnO2 is The SnO2 deposition thickness is 10-40nm; for magnetron sputtering, magnetron sputtering is performed with a 35-90W power RF power supply, and the SnO2 thickness is 20-40nm.
[0037] S3. Prepare a CsPbBr3 perovskite light-absorbing layer on the SnO2 electron transport layer by thermal evaporation. Sequentially evaporate CsBr, PbBr2, CsBr, and PbBr2 precursor films, and then anneal the precursor films at 300-320°C. The thickness of the obtained perovskite is controlled between 500-600nm.
[0038] S4. Prepare the first hole transport layer (such as P3HT) on the CsPbBr3 perovskite layer by slit coating. The concentration of P3HT / chlorobenzene solution is 1-2 mg / mL, the coating rate is 5-10 mm / s, and it is allowed to stand at room temperature until it is completely dry. The thickness of the prepared P3HT hole transport layer is 2-50 nm.
[0039] S5. Prepare a second hole transport layer (such as NiO) on the P3HT hole transport layer by electron beam deposition. X ). NiO X The deposition rate is The annealing temperature is 250-300℃, and the NiO X The thickness of the hole transport layer is 30-40 nm.
[0040] S6. Finally, a transparent conductive electrode is prepared on the double hole transport layer by using a radio frequency power magnetron sputtering method. First, 20-30 nm is deposited at a power of 30-40 W, and then 80-100 nm is deposited at a power of 75-90 W. The transparent conductive electrode is any one of indium tin oxide (ITO), indium zinc oxide (IZO) or indium tungsten oxide (IWO).
[0041] Example 1
[0042] The preparation size is 2cm×1.25cm (such as Figure 6 The process of the inorganic ST-PSC with a double hole transport structure (shown) is as follows:
[0043] (1) Purchase commercial FTO conductive glass from the market and use it as a battery substrate. Gently scrub the glass surface with a non-woven cloth, then ultrasonically clean it with detergent, deionized water, and anhydrous ethanol for 15 minutes each and blow it dry. Then cut it into several 2 cm × 1.25 cm small pieces, use a laser to draw etching lines, distinguish the positive and negative electrodes, and blow it clean.
[0044] (2) The treated FTO conductive glass was immersed in a SnO2 solution with a concentration of 2 mmol / L, and then a SnO2 precursor film was grown on the glass surface by chemical bath deposition in an oven at 83°C. After 2.5 hours, the glass was taken out and annealed at 180°C for 60 minutes to obtain a SnO2 electron transport layer.
[0045] (3) The precursor films of CsBr with a thickness of 120 nm, PbBr2 with a thickness of 170 nm, CsBr with a thickness of 120 nm, and PbBr2 with a thickness of 170 nm were sequentially deposited on the SnO2 electron transport layer at a rate, and then the glass was annealed at 320°C for 20 min and 300°C for 40 min to obtain the CsPbBr3 light absorbing layer.
[0046] (4) A 2 mg / mL P3HT / chlorobenzene solution was coated on the CsPbBr3 light absorbing layer at a rate of 8 mm / s using a slit coating technique and allowed to stand at room temperature until completely dry to obtain a P3HT hole transport layer.
[0047] (5) Electron beam deposition technology was used to prepare NiO on the P3HT hole transport layer in multiple steps X Precursor film, for the first time The deposition rate is 10nm, and the second deposition rate is The deposition rate was 10 nm, and the third time was The precursor film was annealed at 300°C for 60 min to obtain NiO X Hole transport layer.
[0048] (6) Using RF power magnetron sputtering technology on NiO X ITO was deposited on the hole transport layer multiple times, with 20 nm deposited at a power of 35 W for the first time and 80 nm deposited at a power of 85 W for the second time, thereby obtaining an inorganic ST-PSC with a dual hole transport structure.
[0049] Example 2
[0050] The preparation size is 5cm×5cm (such as Figure 7 The process of the inorganic ST-PSC with a double hole transport structure (shown) is as follows:
[0051] (1) Purchase commercial FTO conductive glass from the market and use it as a battery substrate. Gently scrub the glass surface with a non-woven cloth, then ultrasonically clean it with detergent, deionized water, and anhydrous ethanol for 15 minutes each and blow dry, then cut it into several 5 cm × 5 cm small pieces, and use a laser to scratch the P1 etching line (such as Figure 7 As shown), separate into 6 sub-batteries and blow them clean.
[0052] (2) The treated FTO conductive glass was immersed in a SnO2 solution with a concentration of 2 mmol / L, and then a SnO2 precursor film was grown on the glass surface by chemical bath deposition in an oven at 83°C. After 2.5 hours, the glass was taken out and annealed at 180°C for 60 minutes to obtain a SnO2 electron transport layer.
[0053] (3) The precursor films of CsBr with a thickness of 120 nm, PbBr2 with a thickness of 170 nm, CsBr with a thickness of 120 nm, and PbBr2 with a thickness of 170 nm were sequentially deposited on the SnO2 electron transport layer at a rate, and then the glass was annealed at 320°C for 20 min and 300°C for 40 min to obtain the CsPbBr3 light absorbing layer.
[0054] (4) A 2 mg / mL P3HT / chlorobenzene solution was coated on the CsPbBr3 light absorbing layer at a rate of 8 mm / s using a slit coating technique and allowed to stand at room temperature until completely dry to obtain a P3HT hole transport layer.
[0055] (5) Electron beam deposition technology was used to prepare NiO on the P3HT hole transport layer in multiple steps X Precursor film, for the first time The deposition rate is 10nm, and the second deposition rate is The deposition rate was 10 nm, and the third time was The precursor film was annealed at 300°C for 60 min to obtain NiO X Hole transport layer.
[0056] (6) Use a laser to etch the P1 line along the P2 line (such as Figure 7 (shown) removing SnO2 electron transport layer, CsPbBr3 perovskite light absorption layer, P3HT and NiO X The hole transport layer is blown clean, and then the P2 line is placed along the P3 line (such as Figure 7 As shown in the figure, a high-temperature tape with a width of 0.05 mm was pasted, and finally a radio frequency power magnetron sputtering technology was used to deposit NiO X ITO was deposited on the hole transport layer multiple times, with 20 nm deposited at a power of 35 W for the first time and 80 nm deposited at a power of 85 W for the second time, thereby obtaining an inorganic ST-PSC with a dual hole transport structure.
[0057] Example 3
[0058] The preparation size is 10cm×10cm (such as Figure 8 The process of the inorganic ST-PSC with a double hole transport structure (shown) is as follows:
[0059] (1) Purchase commercial FTO conductive glass from the market and use it as a battery substrate. Gently scrub the glass surface with a non-woven cloth, then ultrasonically clean it with detergent, deionized water, and anhydrous ethanol for 15 minutes each and blow it dry. Then cut it into several 10 cm × 10 cm small pieces, use a laser to scribe the P1 etching line, divide it into 12 sub-batteries, and blow it clean.
[0060] (2) The treated FTO conductive glass was immersed in a SnO2 solution with a concentration of 2 mmol / L, and then a SnO2 precursor film was grown on the glass surface by chemical bath deposition in an oven at 83°C. After 2.5 hours, the glass was taken out and annealed at 180°C for 60 minutes to obtain a SnO2 electron transport layer.
[0061] (3) The precursor films of CsBr with a thickness of 120 nm, PbBr2 with a thickness of 170 nm, CsBr with a thickness of 120 nm, and PbBr2 with a thickness of 170 nm were sequentially deposited on the SnO2 electron transport layer at a rate, and then the glass was annealed at 320°C for 20 min and 300°C for 40 min to obtain the CsPbBr3 light absorbing layer.
[0062] (4) A 2 mg / mL P3HT / chlorobenzene solution was coated on the CsPbBr3 light absorbing layer at a rate of 8 mm / s using a slit coating technique and allowed to stand at room temperature until completely dry to obtain a P3HT hole transport layer.
[0063] (5) Electron beam deposition technology was used to prepare NiO on the P3HT hole transport layer in multiple steps X Precursor film, for the first time The deposition rate is 10nm, and the second deposition rate is The deposition rate was 10 nm, and the third time was The precursor film was annealed at 300°C for 60 min to obtain NiO X Hole transport layer.
[0064] (6) Use laser to remove SnO2 electron transport layer, CsPbBr3 perovskite light absorption layer, P3HT and NiO along P2 line above P1 etching line X The hole transport layer was blown clean, and then a high-temperature tape with a width of 0.05 mm was attached along the P3 line above the P2 line. Finally, the RF power magnetron sputtering technology was used to deposit NiOX ITO was deposited on the hole transport layer multiple times, with 20 nm deposited at a power of 35 W for the first time and 80 nm deposited at a power of 85 W for the second time, thereby obtaining an inorganic ST-PSC with a dual hole transport structure.
[0065] The test results show that the semi-transparent battery assembly with a size of 10cm×10cm can output a voltage of 14.03V and a current of 27.3mA.
[0066] Example 4
[0067] The preparation size is 18cm×18cm (such as Fig. 9 The process of the inorganic ST-PSC with a double hole transport structure (shown) is as follows:
[0068] (1) Purchase commercial FTO conductive glass from the market and use it as a battery substrate. Gently scrub the glass surface with a non-woven cloth, then ultrasonically clean it with detergent, deionized water, and anhydrous ethanol for 15 minutes each and blow dry. Then cut it into several 18 cm × 18 cm small pieces, use a laser to scribe the P1 etching line, divide it into 24 sub-batteries, and blow clean.
[0069] (2) The treated FTO conductive glass was immersed in a SnO2 solution with a concentration of 2 mmol / L, and then a SnO2 precursor film was grown on the glass surface by chemical bath deposition in an oven at 83°C. After 2.5 hours, the glass was taken out and annealed at 180°C for 60 minutes to obtain a SnO2 electron transport layer.
[0070] (3) The precursor films of CsBr with a thickness of 120 nm, PbBr2 with a thickness of 170 nm, CsBr with a thickness of 120 nm, and PbBr2 with a thickness of 170 nm were sequentially deposited on the SnO2 electron transport layer at a rate, and then the glass was annealed at 320°C for 20 min and 300°C for 40 min to obtain the CsPbBr3 light absorbing layer.
[0071] (4) A 2 mg / mL P3HT / chlorobenzene solution was coated on the CsPbBr3 light absorbing layer at a rate of 8 mm / s using a slit coating technique and allowed to stand at room temperature until completely dry to obtain a P3HT hole transport layer.
[0072] (5) Electron beam deposition technology was used to prepare NiO on the P3HT hole transport layer in multiple steps X Precursor film, for the first time The deposition rate is 10nm, and the second deposition rate is The deposition rate was 10 nm, and the third time was The precursor film was annealed at 300°C for 60 min to obtain NiOX Hole transport layer.
[0073] (6) Use laser to remove SnO2 electron transport layer, CsPbBr3 perovskite light absorption layer, P3HT and NiO along P2 line above P1 etching line X The hole transport layer was blown clean, and then a high-temperature tape with a width of 0.05 mm was attached along the P3 line above the P2 line. Finally, the RF power magnetron sputtering technology was used to deposit NiO X ITO was deposited on the hole transport layer multiple times, with 20 nm deposited at a power of 35 W for the first time and 80 nm deposited at a power of 85 W for the second time, thereby obtaining an inorganic ST-PSC with a dual hole transport structure.
[0074] The semi-transparent battery assembly with a size of 18cm×18cm is shown in the figure. Fig.10 As shown, the test results show that it can output a voltage of 24.66V and a current of 43.5mA.
[0075] Comparative Example 1
[0076] The process of preparing an inorganic ST-PSC with a size of 2 cm × 1.25 cm is as follows:
[0077] (1) Purchase commercial FTO conductive glass from the market and use it as a battery substrate. Gently scrub the glass surface with a non-woven cloth, then ultrasonically clean it with detergent, deionized water, and anhydrous ethanol for 15 minutes each and blow it dry. Then cut it into several 2 cm × 1.25 cm small pieces, use a laser to draw etching lines, distinguish the positive and negative electrodes, and blow it clean.
[0078] (2) The treated FTO conductive glass was immersed in a SnO2 solution with a concentration of 2 mmol / L, and then a SnO2 precursor film was grown on the glass surface by chemical bath deposition in an oven at 83°C. After 2.5 hours, the glass was taken out and annealed at 180°C for 60 minutes to obtain a SnO2 electron transport layer.
[0079] (3) The precursor films of CsBr with a thickness of 120 nm, PbBr2 with a thickness of 170 nm, CsBr with a thickness of 120 nm, and PbBr2 with a thickness of 170 nm were sequentially deposited on the SnO2 electron transport layer at a rate, and then the glass was annealed at 320°C for 20 min and 300°C for 40 min to obtain the CsPbBr3 light absorbing layer.
[0080] (4) A P3HT / chlorobenzene solution with a concentration of 5 mg / mL was coated on the CsPbBr3 light absorbing layer at a rate of 8 mm / s using a slit coating technique and allowed to stand at room temperature until completely dry to obtain a P3HT hole transport layer.
[0081] (5) Using thermal evaporation technology MoO with a thickness of about 9 nm was deposited on the P3HT hole transport layer at a rate of X Barrier layer.
[0082] (6) Using RF power magnetron sputtering technology on MoO X ITO was deposited on the barrier layer multiple times, with 20 nm deposited at a power of 35 W for the first time and 80 nm deposited at a power of 85 W for the second time, thereby producing an inorganic ST-PSC.
[0083] Comparative Example 2
[0084] The process of preparing an inorganic ST-PSC with a size of 2 cm × 1.25 cm is as follows:
[0085] (1) Purchase commercial FTO conductive glass from the market and use it as a battery substrate. Gently scrub the glass surface with a non-woven cloth, then ultrasonically clean it with detergent, deionized water, and anhydrous ethanol for 15 minutes each and blow it dry. Then cut it into several 2 cm × 1.25 cm small pieces, use a laser to draw etching lines, distinguish the positive and negative electrodes, and blow it clean.
[0086] (2) The treated FTO conductive glass was immersed in a SnO2 solution with a concentration of 2 mmol / L, and then a SnO2 precursor film was grown on the glass surface by chemical bath deposition in an oven at 83°C. After 2.5 hours, the glass was taken out and annealed at 180°C for 60 minutes to obtain a SnO2 electron transport layer.
[0087] (3) The precursor films of CsBr with a thickness of 120 nm, PbBr2 with a thickness of 170 nm, CsBr with a thickness of 120 nm, and PbBr2 with a thickness of 170 nm were sequentially deposited on the SnO2 electron transport layer at a rate, and then the glass was annealed at 320°C for 20 min and 300°C for 40 min to obtain the CsPbBr3 light absorbing layer.
[0088] (4) Electron beam deposition technology was used to prepare NiO on the CsPbBr3 light absorbing layer in multiple steps X Precursor film, for the first time The deposition rate is 10nm, and the second deposition rate is The deposition rate was 10 nm, and the third time was The precursor film was annealed at 300°C for 60 min to obtain NiO X Hole transport layer.
[0089] (5) Using RF power magnetron sputtering technology on NiO XThe hole transport layer was deposited with ITO in multiple times, with 20 nm deposited at 35 W for the first time and 80 nm deposited at 85 W for the second time, thus producing an inorganic ST-PSC.
[0090] In order to fully understand the performance of ST-PSCs prepared in Examples 1-2 and Comparative Examples 1-2, the following tests were performed respectively:
[0091] (1) Analysis of perovskite film morphology
[0092] The test objects are pure perovskite, perovskite covered with P3HT, and perovskite covered with NiO. X Perovskite covered with P3HT and NiO X The perovskite films covered in sequence were characterized by scanning electron microscopy. The test results are as follows Figure 1 As shown, from left to right and from top to bottom, they correspond to the perovskites in Comparative Examples 1-2 and Example 1, where Comparative Example 1 is a perovskite covered with P3HT, and Comparative Example 2 is a perovskite covered with NiO X The perovskite covered in Example 1 is P3HT, NiO X Sequentially covered perovskites.
[0093] Figure 1 The results show that the perovskite protected by the first hole transport layer P3HT is deposited as the second hole transport layer NiO X The film was not damaged, indicating good film quality.
[0094] (2) JV curve test
[0095] The test objects are single P3HT hole transport layer battery, single NiO X The photovoltaic performance of hole transport layer cells, double hole transport layer cells, and double hole transport layer modules (5cm×5cm) was characterized by solar simulators and digital source meters. Figure 2 , 5 As shown, Figure 2 From left to right, they correspond to comparative example 1, comparative example 2, and embodiment 1, Figure 5 Corresponding to Example 2.
[0096] Figure 2 The results show that the perovskite protected by the first hole transport layer P3HT is deposited as the second hole transport layer NiO X After that, it was not destroyed, showing a better performance than P3HT or NiO X Single hole transport layer for better battery performance. Figure 5 The results show that the battery with a double hole transport layer can still maintain good performance when it is enlarged to a size of 5cm×5cm.
[0097] (3) Transmittance test
[0098] The test objects are single P3HT hole transport layer battery, single NiO X The transmittance of the hole transport layer battery and the double hole transport layer battery was characterized by UV-visible spectrophotometer. Figure 3 As shown, the left, middle and right correspond to comparative example 1, comparative example 2 and embodiment 1 respectively.
[0099] Figure 3 The results show that the battery with double hole transport layer can show good light transmission ability, close to that of single NiO X The battery with a hole transport layer is higher than that of the battery with a single P3HT hole transport layer.
[0100] (4) Environmental stability test
[0101] The test objects are single P3HT hole transport layer battery, single NiO X The stability of hole transport layer cells and double hole transport layer cells, the environmental conditions of the cells are: temperature 65℃, relative humidity 55±10%, photovoltaic performance tests are performed every 1 / 2 / 4 days. The test results are as follows Figure 4 As shown, the left, middle and right correspond to comparative example 1, comparative example 2 and embodiment 1 respectively.
[0102] Figure 4 The results show that the battery with double hole transport layer can show good stability, slightly better than that of single NiO X The battery with a hole transport layer is significantly better than the battery with a single P3HT hole transport layer.
[0103] In order to fully understand the battery structure and appearance of Examples 1-4, the following images were taken: Figure 6-9 The photos shown correspond to the batteries in Examples 1 to 4. From the scale, it can be seen that the battery sizes are 2cm×1.25cm, 5cm×5cm, 10cm×10cm, and 18cm×18cm, and the corresponding numbers of sub-batteries are 1, 6, 12, and 24, respectively. It can also be seen that the positions of P1 / P2 / P3 in each large-size component.
[0104] In addition, in order to fully demonstrate the appearance and function of the large-size battery assembly in Example 4, the following Fig.10 The photo shows the light transmission and power generation capabilities of the battery.
[0105] In summary, the inorganic ST-PSC with a double hole transport structure provided by the present invention not only has high light transmittance and photoelectric conversion efficiency, but also can be stably stored in the natural environment and can be easily expanded to a larger area, and is particularly suitable for the field of architectural photovoltaics.
Claims
1. A multi-hole transport structure, characterized in that: The structure at least includes a first hole transport layer and a second hole transport layer, wherein the second hole transport layer is closely attached to the first hole transport layer, wherein the material of the first hole transport layer is selected from any one of Spiro-OMeTAD, PTAA, and P3HT, and the material of the second hole transport layer is selected from NiO X 、CuI、CuO X , any one of V2O5.
2. The multi-hole transport structure according to claim 1, wherein: The thickness of the first hole transport layer is 2nm-50nm, and the thickness of the second hole transport layer is 10nm-40nm.
3. The method for preparing the multi-hole transport structure according to any one of claims 1 to 2, characterized in that The method comprises: preparing a first hole transport layer on a substrate by slit coating, and preparing a second hole transport layer on the surface of the first hole transport layer by electron beam deposition or radio frequency power magnetron sputtering technology.
4. The method according to claim 3, characterized in that: The preparation process of the first hole transport layer is as follows: Spiro-OMeTAD, PTAA, P3HT and an organic solvent are evenly mixed to obtain a solution with a concentration of 1-5 g / L, and then the solution is coated on the substrate at a rate of 5-10 mm / s using a slit coating technique, and the first hole transport layer is obtained after sufficient drying.
5. The method according to claim 3, characterized in that: The preparation process of the second hole transport layer is as follows: NiO is deposited on the substrate several times by electron beam deposition or magnetron sputtering technology. X 、CuI、CuO X , V2O5 is deposited on the surface of the first hole transport layer to obtain a second hole transport layer.
6. The method according to claim 5, characterized in that: The deposition times are three times and the deposition speed is different each time. The specific deposition speeds are:
7. An inorganic light-transmitting solar cell based on a multi-hole transport structure, characterized in that: The battery comprises, from bottom to top or from top to bottom, a transparent conductive substrate, an electron transport layer, a perovskite light absorption layer, a first hole transport layer, a second hole transport layer, and a transparent conductive electrode.
8. The inorganic light-transmitting solar cell according to claim 7, characterized in that: The transparent conductive substrate is specifically FTO or ITO glass, the perovskite light absorbing layer is specifically CsPbBr3, and the transparent conductive electrode is specifically ITO, IZO, or IWO.
9. The inorganic light-transmitting solar cell according to claim 7, characterized in that: The thickness of the electron transport layer is 10nm-20nm, and the thickness of the perovskite light absorption layer is 500nm-600nm.
10. The method for preparing an inorganic light-transmitting solar cell according to any one of claims 7 to 9, characterized in that The method comprises: washing and drying a transparent conductive substrate, preparing an electron transport layer on its surface by chemical bath deposition, spraying, atomic layer deposition or magnetron sputtering technology, then preparing a perovskite light absorption layer on the surface of the electron transport layer by thermal evaporation, then preparing a first hole transport layer and a second hole transport layer in sequence on the surface of the perovskite light absorption layer, and finally preparing a transparent conductive electrode on the second hole transport layer by magnetron sputtering or atomic layer deposition technology.